TeKnow: a knowledgeable game for kids / Wan Anisha Wan Mohammad, Rafizah Kechil and Azlina Mohd Mydin - Wan Mohammad, Wan Anisha; Kechil, Rafizah; Mohd Mydin, Azlina (Unit Penerbitan JSKM, 2023)
In the era of technology and globalization, teaching and learning has play an important role in human life especially when involving the new generations. To make teaching and learning more interesting, new attempt have been made by introducing gaming concepts to students. During recent years, more classical concepts are being introduced in teaching and learning by using board games. Thus, TeKnow was being developed to test students' knowledge and understanding while playing games. TeKnow was inspired by the Snakes and Ladders game. It was specifically designed for school students from different ages. Simple questions on English will be asked to increase students' knowledge on vocabulary and spelling according to different level of difficulties. Through this game, player do not only have fun but at the same time they can learn to test their knowledge on spelling and vocabulary. Besides that, students have to take turns to express their ideas according to the instructions given. This game is hoped to help teachers and students in teaching and learning especially to develop students social skills and increase understanding and flexibility in their studies.